Pethidine in Low Doses versus Dipyrone for Pain Relief in Labor: A Randomized Controlled Trial - Rogevando Rodrigues Nunes; André Montenegro Primo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To compare low doses of pethidine with dipyrone in labor analgesia. Methods In a randomized prospective study conducted by Universidade de Fortaleza, in the state of Ceará, Brazil, between May and December 2016, 200 full-term parturients, with very painful uterine contractions and exhibiting uterine cervix dilatation ≥ 5 cm, were selected to receive a single intravenous dose of either 0.25 mg/kg of pethidine (n = 100) or of 25 mg/kg of dipyrone (n = 100). Pain was assessed using the visual analogue scale. The data were analyzed using the Student t-test, the chi-square test and the likelihood ratio. Results There was a significant improvement in pain in 35% of the parturients. Both drugs presented a similar analgesic effect 1 hour after the intervention (p = 0.692). There was no analgesic effect during the evaluation of the second hour after the intervention with pethidine or dipyrone. There were no adverse effects, such as maternal drowsiness, nausea or vomiting, related to the drugs used. Conclusion Pethidine in low doses and dipyrone presented equivalent analgesia during labor. Public Registry of Clinical TrialsRBR-4hsyy4.